Coating liquid manufacturing method and heat insulating material manufacturing method

By aggregating airgel particles with a water-soluble polymer in a liquid medium, the method addresses resin penetration into airgel pores, enhancing heat insulation and film strength in the resulting heat insulating material.

JP7616081B2Active Publication Date: 2025-01-17RESONAC CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021574711
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2021-01-29
Publication Date
2025-01-17
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

When airgel particles are dispersed in a resin component to form a coating liquid, the resin component penetrates into the pores of the airgel particles, leading to a loss of pore structure, reduced insulation properties, and insufficient film strength, resulting in cracks.

Method used

A method involving the aggregation of airgel particles with a water-soluble polymer having a hydrophobic group and a liquid medium to form a coating liquid, which reduces the contact interface between airgel particles and resin, preventing resin penetration into the pores and ensuring uniform dispersion of airgel particles.

Benefits of technology

The method produces a coating liquid that results in a heat insulating material with high heat insulation and film forming properties, minimizing resin penetration into airgel pores and preventing uneven coating and cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616081000001
    Figure 0007616081000001
  • Figure 0007616081000002
    Figure 0007616081000002
  • Figure 0007616081000003
    Figure 0007616081000003
Patent Text Reader

Abstract

This manufacturing method for a coating liquid comprises: a preparation step for preparing aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium; and a mixing step for mixing the aerogel particles, the water-soluble polymer, and the liquid medium prepared in the preparation step and aggregating the aerogel particles to obtain a coating liquid containing the aggregate of the aerogel particles, the water-soluble polymer and the liquid medium.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a coating liquid and a method for producing a heat insulating material. [Background technology]

[0002] Aerogel is known as a material with excellent thermal insulation properties. In addition, a method has been proposed in which aerogel is processed into particles and used as a constituent material of a thermal insulation material (for example, Patent Documents 1 and 2). Patent Document 1 proposes using particulate aerogel as a filler between resin plates that constitute a thermal insulation window. Patent Document 2 shows a method of producing a thermal insulation material (molded body) by preparing an aqueous dispersion containing aerogel particles and organic fibers, and then evaporating the water to obtain an intermediate product, which is then press-molded. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-91943 A [Patent Document 2] JP 2014-35044 A Summary of the Invention [Problem to be solved by the invention]

[0004] Composite materials in which aerogel particles are dispersed in a resin component are expected to have excellent heat resistance. However, when such composite materials are made into coating liquid, there are problems such as the resin component penetrating into the pores of the aerogel particles, causing the pore structure to be lost and the insulation properties to decrease, and the coating film not being strong enough and prone to cracking.

[0005] Therefore, the present invention aims to provide a method for producing a heat insulating material, which can suppress the penetration of a resin component into the pores of the aerogel particles and can obtain a heat insulating material having high heat insulating properties and high film forming properties. Another object of the present invention is to provide a coating liquid for forming the heat insulating material and a method for producing the coating liquid. [Means for solving the problem]

[0006] One aspect of the present invention relates to a method for producing a coating liquid, the method including: a preparation step of preparing aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium; and a mixing step of mixing the aerogel particles, the water-soluble polymer, and the liquid medium prepared in the preparation step to aggregate the aerogel particles, thereby obtaining a coating liquid containing the aggregates of the aerogel particles, the water-soluble polymer, and the liquid medium.

[0007] In the coating liquid obtained by the above manufacturing method, the contact interface between the aerogel particles and the resin component is reduced due to the aggregation of the aerogel particles, and the penetration of the resin component into the pores of the aerogel particles is suppressed. In addition, the coating liquid obtained by the above manufacturing method is not a mixture of aerogel particle aggregates prepared in advance, but is a mixture of aerogel particles aggregated when mixed with other components, so that the aerogel particles and their aggregates are uniformly dispersed, and unevenness of the coating film, cracking, etc. due to uneven distribution of the aerogel particles can be suppressed. Furthermore, in the above manufacturing method, since a water-soluble polymer having a hydrophobic group is used as the resin component, the dispersibility of the aerogel particles is further improved, and a coating liquid in which the aerogel particles and their aggregates are uniformly dispersed can be obtained even when the filling rate of the aerogel particles is increased. Therefore, a heat insulating material having high heat insulating properties and high film forming properties can be obtained by the coating liquid obtained by the above manufacturing method.

[0008] In one embodiment, the average diameter of the aggregates may be 2 to 40 times the average diameter of the aerogel particles prepared in the preparation step. By forming such aggregates, the above-mentioned effects are more significantly exhibited.

[0009] In one embodiment, when the diluted solution obtained by diluting the coating liquid is observed under an optical microscope, the area occupied by the aerogel particles and the aggregates within the observation field may be 50% or more, whereby the above-mentioned effects are more pronounced.

[0010] In one embodiment, the total content of the aerogel particles and the aggregates in the coating liquid may be 70% by volume or more based on the total volume of the solid content.

[0011] In one embodiment, the water-soluble polymer may include a cellulose-based resin.

[0012] Another aspect of the present invention relates to a method for producing a heat insulating material, the method including a coating step of coating a support with the coating liquid produced by the above-mentioned production method to obtain a coating film, and a removal step of removing at least a part of the liquid medium from the coating film to obtain a heat insulating material. According to such a production method, the penetration of the resin component into the pores of the aerogel particles is suppressed, and a heat insulating material having high heat insulating properties and high film forming properties can be easily obtained.

[0013] In one embodiment, the pore volume of the insulation is less than 0.15 cm 3 / g or more.

[0014] Yet another aspect of the present invention relates to a coating liquid containing an aggregate of aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium, wherein when the coating liquid is diluted and a diluted liquid is observed under an optical microscope, an area occupied by the aerogel particles and the aggregates within the observation field is 50% or more of an area occupied by the aggregates having a diameter of 20 μm or more. Effect of the Invention

[0015] According to the present invention, there is provided a method for producing a heat insulating material, which can suppress the penetration of a resin component into the pores of the aerogel particles and can obtain a heat insulating material having high heat insulating properties and high film forming properties. Also, according to the present invention, there is provided a method for producing a coating liquid, which can easily produce a coating liquid for forming the heat insulating material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Preferred embodiments of the present invention will be described in detail below. However, the present invention is not limited to the following embodiments. In this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​before and after "~" as the minimum and maximum values, respectively. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this embodiment may be used alone or in combination of two or more.

[0017] The method for producing a coating liquid according to this embodiment includes a preparation step of preparing aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium, and a mixing step of mixing the aerogel particles, the water-soluble polymer, and the liquid medium prepared in the preparation step to aggregate the aerogel particles, thereby obtaining a coating liquid containing aggregates of aerogel particles, the water-soluble polymer, and the liquid medium.

[0018] In the coating liquid obtained by the manufacturing method of this embodiment, the contact interface between the aerogel particles and the resin component is reduced due to the aggregation of the aerogel particles, and the penetration of the resin component into the pores of the aerogel particles is suppressed. In order to reduce the contact interface, it is possible to prepare an aggregate of aerogel particles in advance, but in this case, it is difficult to disperse the aggregate in the coating liquid, and there is a risk that the aggregate will break down due to a stirring operation for dispersion. In this embodiment, the aerogel particles are aggregated when mixed with other components, so that the aerogel particles and their aggregates are uniformly dispersed, and unevenness and cracking of the coating film due to uneven distribution of the aerogel particles are suppressed. In addition, in this embodiment, the dispersibility of the aerogel particles is further improved by using a water-soluble polymer having a hydrophobic group as the resin component, and a coating liquid in which the aerogel particles and their aggregates are uniformly dispersed can be obtained even when the filling rate of the aerogel particles is increased. Therefore, according to the manufacturing method of this embodiment, a coating liquid capable of forming a heat insulating material having high heat insulation and high film forming properties can be obtained.

[0019] The method for producing a heat insulating material according to the present embodiment includes a coating step of applying the coating liquid produced by the above method onto a support to obtain a coating film, and a removal step of removing at least a part of the liquid medium from the coating film to obtain a heat insulating material. The method for producing a heat insulating material according to the present embodiment may further include a coating liquid production step of obtaining a coating liquid by the above method.

[0020] According to the manufacturing method of this embodiment, the penetration of the resin component into the pores of the aerogel particles is suppressed, and a thermal insulation material having high thermal insulation properties and high film-forming properties can be easily obtained.

[0021] <Aerogel> In the narrow sense, a dry gel obtained by using a supercritical drying method on a wet gel is called an aerogel, a dry gel obtained by drying under atmospheric pressure is called a xerogel, and a dry gel obtained by freeze-drying is called a cryogel. In this embodiment, however, a low-density dry gel obtained regardless of these drying methods of a wet gel is called an "aerogel". That is, in this embodiment, "aerogel" means "gel comprised of a microporous solid in which the dispersed phase is a gas (gel composed of a microporous solid in which the dispersed phase is a gas)" which is an aerogel in the broad sense. In general, the inside of an aerogel has a mesh-like fine structure and has a cluster structure in which particulate aerogel components of about 2 to 20 nm are bonded. Between the skeletons formed by these clusters, there are pores of less than 100 nm. As a result, the aerogel has a three-dimensional fine porous structure.

[0022] The aerogel according to the present embodiment is, for example, a silica aerogel mainly composed of silica. Examples of the silica aerogel include so-called organic-inorganic hybrid silica aerogels into which an organic group (such as a methyl group) or an organic chain is introduced.

[0023] Examples of the aerogel according to this embodiment include the following aspects. By adopting these aspects, it is easy to obtain an aerogel that is excellent in heat insulation, flame retardancy, heat resistance, and flexibility. By adopting each aspect, it is possible to obtain an aerogel that has heat insulation, flame retardancy, heat resistance, and flexibility according to each aspect.

[0024] (First aspect) The aerogel according to this embodiment can have a structure represented by the following general formula (1): The aerogel according to this embodiment can have a structure represented by the following general formula (1a) as a structure including the structure represented by formula (1). [ka] [ka]

[0025] In formula (1) and formula (1a), R 1 and R 2 each independently represents an alkyl group or an aryl group; R 3 and R 4 Each of R independently represents an alkylene group. Examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. p represents an integer of 1 to 50. In formula (1a), when two or more R 1 may be the same or different, and similarly, two or more R 2 may be the same or different. In formula (1a), two R 3 may be the same or different, and similarly, two R 4 may be the same or different.

[0026] By introducing the structure represented by the above formula (1) or formula (1a) into the skeleton of an aerogel as an aerogel component, an aerogel having low thermal conductivity and flexibility can be obtained.1 and R 2 Each of R independently represents an alkyl group having 1 to 6 carbon atoms, a phenyl group, etc., and the alkyl group may be a methyl group, etc. 3 and R 4 are each independently an alkylene group having 1 to 6 carbon atoms, and examples of the alkylene group include an ethylene group, a propylene group, etc. In formula (1a), p can be an integer of 2 to 30, and may be an integer of 5 to 20.

[0027] (Second Aspect) The aerogel according to this embodiment has a ladder structure having struts and bridges, and the bridges can have a structure represented by the following general formula (2). By introducing such a ladder structure as an aerogel component into the skeleton of the aerogel, the heat resistance and mechanical strength can be improved. In this embodiment, the "ladder structure" refers to a structure having two struts and bridges connecting the struts (having a so-called "ladder" shape). In this embodiment, the skeleton of the aerogel may have a ladder structure, but the aerogel may also have a ladder structure partially. [ka]

[0028] In formula (2), R 5 and R 6 Each independently represents an alkyl group or an aryl group, and b represents an integer of 1 to 50. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. In addition, in the formula (2), when b is an integer of 2 or more, two or more R 5 may be the same or different, and similarly, two or more R 6 may be the same or different.

[0029] By introducing the above structure into the skeleton of an aerogel as an aerogel component, an aerogel having superior flexibility to, for example, an aerogel having a structure derived from a conventional ladder-type silsesquioxane (i.e., a structure represented by the following general formula (X)) can be obtained. Silsesquioxane has the composition formula: (RSiO 1.5 ) n It is a polysiloxane having the above structure, and can have various skeletal structures such as a cage type, a ladder type, and a random type. As shown in the following general formula (X), in an aerogel having a structure derived from a conventional ladder type silsesquioxane, the structure of the bridge portion is -O-, but in the aerogel according to this embodiment, the structure of the bridge portion is the structure represented by the above general formula (2) (polysiloxane structure). However, the aerogel of this embodiment may further have a structure derived from silsesquioxane in addition to the structure represented by the general formula (2). [ka]

[0030] In formula (X), R represents a hydroxy group, an alkyl group, or an aryl group.

[0031] The structure that serves as the support portion and its chain length, as well as the spacing between the structures that serve as the bridging portions are not particularly limited. From the viewpoint of further improving heat resistance and mechanical strength, the ladder structure may have a ladder structure represented by the following general formula (3). [ka]

[0032] In formula (3), R 5 , R 6 , R 7 and R 8each independently represents an alkyl group or an aryl group, a and c each independently represent an integer of 1 to 3000, and b represents an integer of 1 to 50. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. In addition, when b is an integer of 2 or more in formula (3), two or more R 5 may be the same or different, and similarly, two or more R 6 In addition, in formula (3), when a is an integer of 2 or more, there are two or more R 7 may be the same or different, and similarly, when c is an integer of 2 or more, two or more R 8 may be the same or different.

[0033] In order to obtain better flexibility, R 5 , R 6 , R 7 and R 8 (However, R 7 and R 8 (only in formula (3)) each independently includes an alkyl group having 1 to 6 carbon atoms, a phenyl group, etc., and the alkyl group includes a methyl group, etc. In formula (3), a and c each independently can be 6 to 2000, but may be 10 to 1000. In formulas (2) and (3), b can be 2 to 30, but may be 5 to 20.

[0034] (Third Aspect) The aerogel according to this embodiment may be a dried product of a wet gel which is a condensate of a sol containing at least one selected from the group consisting of a silicon compound having a hydrolyzable functional group or a condensable functional group, and a hydrolysis product of a silicon compound having a hydrolyzable functional group (obtained by drying a wet gel generated from a sol: dried product of a wet gel derived from a sol). The aerogel described above may also be obtained by drying a wet gel generated from a sol containing a silicon compound or the like in this way.

[0035] As the silicon compound having a hydrolyzable functional group or a condensable functional group, a polysiloxane compound can be used. That is, the sol can contain at least one compound selected from the group consisting of a polysiloxane compound having a hydrolyzable functional group or a condensable functional group, and a hydrolysis product of a polysiloxane compound having a hydrolyzable functional group (hereinafter, sometimes referred to as a "polysiloxane compound group").

[0036] The functional group in the polysiloxane compound is not particularly limited, but may be a group that reacts with the same functional group or reacts with another functional group. Examples of hydrolyzable functional groups include alkoxy groups. Examples of condensable functional groups include hydroxyl groups, silanol groups, carboxyl groups, and phenolic hydroxyl groups. The hydroxyl group may be contained in a hydroxyl group-containing group such as a hydroxyalkyl group. The polysiloxane compound having a hydrolyzable functional group or a condensable functional group may further have a reactive group (a functional group that does not fall under the category of hydrolyzable functional group and condensable functional group) different from the hydrolyzable functional group and the condensable functional group. Examples of the reactive group include an epoxy group, a mercapto group, a glycidoxy group, a vinyl group, an acryloyl group, a methacryloyl group, and an amino group. The epoxy group may be contained in an epoxy group-containing group such as a glycidoxy group. The polysiloxane compound having these functional groups and reactive groups may be used alone or in a mixture of two or more types. Among these functional groups and reactive groups, for example, groups that improve the flexibility of the aerogel include alkoxy groups, silanol groups, hydroxyalkyl groups, etc., and among these, alkoxy groups and hydroxyalkyl groups can further improve the compatibility of the sol. In addition, from the viewpoint of improving the reactivity of the polysiloxane compound and reducing the thermal conductivity of the aerogel, the number of carbon atoms of the alkoxy group and hydroxyalkyl group can be 1 to 6, but from the viewpoint of further improving the flexibility of the aerogel, it may be 2 to 5 or 2 to 4.

[0037] Examples of polysiloxane compounds having a hydroxyalkyl group in the molecule include those having a structure represented by the following general formula (A): By using a polysiloxane compound having a structure represented by the following general formula (A), the structures represented by general formulas (1) and (1a) can be introduced into the skeleton of an aerogel. [ka]

[0038] In formula (A), R 1a represents a hydroxyalkyl group, and R 2a represents an alkylene group, and R 3a and R 4a Each of R independently represents an alkyl group or an aryl group, and n represents an integer of 1 to 50. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. In addition, in formula (A), when two R 1a may be the same or different, and similarly, two R 2a may be the same or different. In addition, in formula (A), two or more R 3a may be the same or different, and similarly, two or more R 4a may be the same or different.

[0039] By using a wet gel (produced from a sol) that is a condensate of a sol containing a polysiloxane compound having the above structure, it becomes easier to obtain an aerogel that has low thermal conductivity and is flexible. 1a Examples of the hydroxyalkyl group include a hydroxyethyl group and a hydroxypropyl group. 2a Examples of the alkylene group include an alkylene group having 1 to 6 carbon atoms, and examples of the alkylene group include an ethylene group and a propylene group. 3a and R 4aEach of the alkyl groups independently includes an alkyl group having 1 to 6 carbon atoms, a phenyl group, etc., and examples of the alkyl group include a methyl group, etc. In addition, in the formula (A), n can be 2 to 30, but may also be 5 to 20.

[0040] As the polysiloxane compound having the structure represented by the above general formula (A), commercially available products can be used, and examples thereof include compounds such as X-22-160AS, KF-6001, KF-6002, and KF-6003 (all manufactured by Shin-Etsu Chemical Co., Ltd.), and compounds such as XF42-B0970 and Fluid OFOH 702-4% (all manufactured by Momentive Corporation).

[0041] Examples of polysiloxane compounds having an alkoxy group in the molecule include those having a structure represented by the following general formula (B): By using a polysiloxane compound having a structure represented by the following general formula (B), a ladder structure having a bridge portion represented by general formula (2) or (3) can be introduced into the skeleton of an aerogel. [ka]

[0042] In formula (B), R 1b represents an alkyl group, an alkoxy group, or an aryl group; R 2b and R 3b each independently represents an alkoxy group; R 4b and R 5b Each of R independently represents an alkyl group or an aryl group, and m represents an integer of 1 to 50. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. In addition, in formula (B), two R 1b may be the same or different, and two R 2b may be the same or different, and similarly, two R 3b may be the same or different. In addition, in formula (B), when m is an integer of 2 or more, there are two or more R4b may be the same or different, and similarly, two or more R 5b may be the same or different.

[0043] By using a wet gel (produced from a sol) that is a condensate of a sol containing the polysiloxane compound having the above structure or a hydrolysis product thereof, it becomes easier to obtain an aerogel that has low thermal conductivity and is flexible. 1b Examples of the alkyl group or alkoxy group include a methyl group, a methoxy group, and an ethoxy group. 2b and R 3b are each independently an alkoxy group having 1 to 6 carbon atoms, and examples of the alkoxy group include a methoxy group and an ethoxy group. 4b and R 5b are each independently an alkyl group having 1 to 6 carbon atoms, a phenyl group, etc., and the alkyl group is a methyl group, etc. In addition, in formula (B), m can be 2 to 30, but may also be 3 to 35, or 5 to 20.

[0044] The polysiloxane compound having the structure represented by the above general formula (B) can be obtained by appropriately referring to the production methods reported in JP-A-2000-26609, JP-A-2012-233110, etc. In addition, XR31-B1410 (manufactured by Momentive Corp.) can also be used as the polysiloxane compound.

[0045] In addition, since the alkoxy group is hydrolyzed, the polysiloxane compound having the alkoxy group may exist as a hydrolysis product in the sol, and the polysiloxane compound having the alkoxy group and its hydrolysis product may be mixed. In addition, in the polysiloxane compound having the alkoxy group, all of the alkoxy groups in the molecule may be hydrolyzed, or may be partially hydrolyzed.

[0046] These polysiloxane compounds having a hydrolyzable functional group or a condensable functional group and the hydrolysis products of the polysiloxane compounds having a hydrolyzable functional group may be used alone or in combination of two or more kinds.

[0047] In preparing the aerogel according to this embodiment, silicon compounds having hydrolyzable functional groups or condensable functional groups can be silicon compounds other than the polysiloxane compounds described above. That is, the sol containing the silicon compounds described above can contain at least one selected from the group consisting of silicon compounds having hydrolyzable functional groups or condensable functional groups (excluding polysiloxane compounds) and hydrolysis products of the silicon compounds having hydrolyzable functional groups (hereinafter, sometimes referred to as "silicon compounds") in addition to the polysiloxane compounds described above, or instead of the polysiloxane compounds described above. The number of silicon atoms in the molecule of the silicon compound can be 1 or 2.

[0048] Silicon compounds having hydrolyzable functional groups in the molecule include, but are not limited to, alkyl silicon alkoxides. The number of hydrolyzable functional groups in the alkyl silicon alkoxides can be 3 or less from the viewpoint of improving water resistance. Examples of such alkyl silicon alkoxides include monoalkyl trialkoxysilanes, monoalkyl dialkoxysilanes, dialkyl dialkoxysilanes, monoalkyl monoalkoxysilanes, dialkyl monoalkoxysilanes, trialkyl monoalkoxysilanes, and the like, and more specifically, methyl trimethoxysilane, methyl dimethoxysilane, dimethyl diethoxysilane, dimethyl dimethoxysilane, ethyl trimethoxysilane, hexyl trimethoxysilane, and the like. Here, examples of the hydrolyzable functional groups include alkoxy groups such as methoxy and ethoxy groups.

[0049] Examples of silicon compounds having a condensable functional group include, but are not limited to, silanetetraol, methylsilanetriol, dimethylsilanediol, phenylsilanetriol, phenylmethylsilanediol, diphenylsilanediol, n-propylsilanetriol, hexylsilanetriol, octylsilanetriol, decylsilanetriol, and trifluoropropylsilanetriol.

[0050] The silicon compound having a hydrolyzable functional group or a condensable functional group may further have the above-mentioned reactive group different from the hydrolyzable functional group and the condensable functional group (a functional group other than the hydrolyzable functional group and the condensable functional group).

[0051] Examples of silicon compounds having three or less hydrolyzable functional groups and a reactive group include vinyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, and N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane.

[0052] In addition, examples of silicon compounds having a condensable functional group and a reactive group that can be used include vinyl silanetriol, 3-glycidoxypropyl silanetriol, 3-glycidoxypropyl methyl silanediol, 3-methacryloxypropyl silanetriol, 3-methacryloxypropyl methyl silanediol, 3-acryloxypropyl silanetriol, 3-mercaptopropyl silanetriol, 3-mercaptopropyl methyl silanediol, N-phenyl-3-aminopropyl silanetriol, and N-2-(aminoethyl)-3-aminopropyl methyl silanediol.

[0053] Furthermore, silicon compounds having three or less hydrolyzable functional groups at the molecular terminals, such as bistrimethoxysilylmethane, bistrimethoxysilylethane, bistrimethoxysilylhexane, ethyltrimethoxysilane, and vinyltrimethoxysilane, can also be used.

[0054] The silicon compounds (excluding polysiloxane compounds) having a hydrolyzable functional group or a condensable functional group, and the hydrolysis products of the silicon compounds having a hydrolyzable functional group may be used alone or in combination of two or more kinds.

[0055] By using the above silicon compounds (excluding polysiloxane compounds), structures represented by the following general formulas (4) to (6) can be introduced into the skeleton of the aerogel. The aerogel according to this embodiment can have any one of these structures alone, or two or more of them.

[0056] [ka]

[0057] In formula (4), R 9 represents an alkyl group. Here, examples of the alkyl group include alkyl groups having 1 to 6 carbon atoms, and examples of the alkyl group include a methyl group.

[0058] [ka]

[0059] In formula (5), R 10 and R 11 each independently represents an alkyl group. Examples of the alkyl group include alkyl groups having 1 to 6 carbon atoms, and examples of the alkyl group include a methyl group.

[0060] [ka]

[0061] In formula (6), R 12 represents an alkylene group. Examples of the alkylene group include alkylene groups having 1 to 10 carbon atoms, and examples of the alkylene group include an ethylene group and a hexylene group.

[0062] (Fourth aspect) The aerogel according to the present embodiment may further contain silica particles in addition to the aerogel component in order to further increase toughness and to achieve even better heat insulation and flexibility. An aerogel containing an aerogel component and silica particles can also be called an aerogel composite. Although the aerogel composite is a composite of the aerogel component and the silica particles, it has a cluster structure that is characteristic of aerogel and is considered to have a three-dimensional fine porous structure.

[0063] The aerogel containing the aerogel component and silica particles can be said to be a dried product of a wet gel which is a condensation product of a sol containing at least one selected from the group consisting of a silicon compound having a hydrolyzable functional group or a condensable functional group, and a hydrolysis product of a silicon compound having a hydrolyzable functional group, and silica particles. Therefore, the description of the first to third aspects can be appropriately applied to the aerogel according to this embodiment.

[0064] The silica particles can be used without any particular limitation, and include amorphous silica particles. The amorphous silica particles can be fused silica particles, fumed silica particles, colloidal silica particles, etc. Among them, colloidal silica particles have high monodispersity and are easy to suppress aggregation in sol. The silica particles may be silica particles having a hollow structure, a porous structure, etc.

[0065] The shape of the silica particles is not particularly limited, and examples thereof include spherical, cocoon-shaped, and association-shaped. Among these, by using spherical particles as the silica particles, aggregation in the sol can be easily suppressed. The average primary particle diameter of the silica particles may be 1 nm or more, 5 nm or more, or 20 nm or more from the viewpoint of easily imparting appropriate strength and flexibility to the aerogel and easily obtaining an aerogel having excellent shrinkage resistance during drying. The average primary particle diameter of the silica particles may be 500 nm or less, 300 nm or less, or 100 nm or less from the viewpoint of easily suppressing the solid thermal conduction of the silica particles and easily obtaining an aerogel having excellent heat insulation. From these viewpoints, the average primary particle diameter of the silica particles may be 1 to 500 nm, 5 to 300 nm, or 20 to 100 nm.

[0066] In this embodiment, the average particle size of the aerogel components and the average primary particle size of the silica particles can be obtained by directly observing the aerogel using a scanning electron microscope (hereinafter abbreviated as "SEM"). The "diameter" here means the diameter when the cross section of the particle exposed on the cross section of the aerogel is regarded as a circle. In addition, the "diameter when the cross section is regarded as a circle" means the diameter of the perfect circle when the area of ​​the cross section is replaced with a perfect circle of the same area. In addition, when calculating the average particle size, the diameter of the circle is calculated for 100 particles and the average is taken.

[0067] The average particle size of silica particles can also be measured from the raw material. For example, the biaxial average primary particle size is calculated from the results of observing 20 arbitrary particles by SEM as follows. That is, taking colloidal silica particles dispersed in water with a normal solid content concentration of about 5 to 40% by mass as an example, a chip obtained by cutting a wafer with pattern wiring into 2 cm squares is immersed in a dispersion of colloidal silica particles for about 30 seconds, and then the chip is rinsed with pure water for about 30 seconds and dried by nitrogen blow. Thereafter, the chip is placed on a sample stage for SEM observation, an accelerating voltage of 10 kV is applied, and the silica particles are observed at a magnification of 100,000 times, and an image is taken. 20 silica particles are arbitrarily selected from the obtained image, and the average of the particle sizes of those particles is taken as the average particle size.

[0068] The number of silanol groups per 1 g of silica particles is set to 10 × 10 from the viewpoint of easily obtaining an aerogel with excellent shrinkage resistance. 18 The number of pieces / g or more may be 50×10 18 The number of pieces / g or more may be 100×10 18 The number of silanol groups per 1 g of silica particles may be 1000×10 18 It may be 800×10 18 It may be 700×10 18 From these viewpoints, the number of silanol groups per gram of silica particles may be 10 × 10 18 ~1000×10 18 50×10 18 ~800×10 18 It may be 100×10 18 ~700×10 18 It may be pieces / g.

[0069] The content of the polysiloxane compound group contained in the sol (the content of the polysiloxane compound having a hydrolyzable functional group or a condensable functional group, and the total content of the hydrolysis product of the polysiloxane compound having a hydrolyzable functional group) may be 5 parts by mass or more, or 10 parts by mass or more, relative to 100 parts by mass of the total amount of the sol, from the viewpoint of further facilitating obtaining good reactivity. The content of the polysiloxane compound group contained in the sol may be 50 parts by mass or less, or 30 parts by mass or less, relative to 100 parts by mass of the total amount of the sol, from the viewpoint of further facilitating obtaining good compatibility. From these viewpoints, the content of the polysiloxane compound group contained in the sol may be 5 to 50 parts by mass, or 10 to 30 parts by mass, relative to 100 parts by mass of the total amount of the sol.

[0070] When the sol contains a silicon compound (excluding polysiloxane compounds), the silicon compound group (the content of the silicon compound having a hydrolyzable functional group or a condensable functional group, and the total content of the hydrolysis product of the silicon compound having a hydrolyzable functional group) may be 5 parts by mass or more, 7 parts by mass or more, or 10 parts by mass or more relative to 100 parts by mass of the total amount of the sol, from the viewpoint of further facilitating obtaining good reactivity. The content of the silicon compound group contained in the sol may be 50 parts by mass or less, 40 parts by mass or less, or 30 parts by mass or less relative to 100 parts by mass of the total amount of the sol, from the viewpoint of further facilitating obtaining good compatibility.

[0071] When the sol contains both a polysiloxane compound group and a silicon compound group, the ratio of the content of the polysiloxane compound group to the content of the silicon compound group may be 1:0.5 or more, 1:0.7 or more, or 1:1 or more from the viewpoint of further facilitating obtaining good compatibility. The ratio of the content of the polysiloxane compound group to the content of the silicon compound group may be 1:4 or less, 1:3 or less, or 1:2 or less from the viewpoint of further facilitating suppression of gel shrinkage. From these viewpoints, the ratio of the content of the polysiloxane compound group to the content of the silicon compound group may be 1:0.5 to 1:4, 1:0.7 to 1:3, or 1:1 to 1:2.

[0072] When the sol contains silica particles, the content of the silica particles may be 1 part by mass or more, 2 parts by mass or more, or 4 parts by mass or more relative to 100 parts by mass of the total amount of the sol, from the viewpoint of easily imparting a suitable strength to the aerogel and easily obtaining an aerogel having excellent shrinkage resistance during drying. The content of the silica particles may be 20 parts by mass or less, 17 parts by mass or less, or 15 parts by mass or less relative to 100 parts by mass of the total amount of the sol, from the viewpoint of easily suppressing the solid thermal conduction of the silica particles and easily obtaining an aerogel having excellent heat insulation. From these viewpoints, the content of the silica particles may be 1 to 20 parts by mass, 2 to 17 parts by mass, or 4 to 15 parts by mass relative to 100 parts by mass of the total amount of the sol.

[0073] <Aerogel particles> The aerogel particles in this embodiment can be obtained, for example, by pulverizing a bulk aerogel as described later.

[0074] The average particle size D50 of the aerogel particles (also referred to as the average diameter) can be 0.1 to 1000 μm, but may be 0.5 to 700 μm, 1 to 500 μm, 3 to 100 μm, or 5 to 50 μm. When the average particle size D50 of the aerogel particles is large, it is easy to obtain aerogel particles with excellent dispersibility, handleability, etc. On the other hand, when the average particle size D50 is small, it is easy to obtain aerogel particles with excellent dispersibility. The average particle size of the aerogel particles can be appropriately adjusted by the pulverization method and pulverization conditions, sieve, classification method, etc.

[0075] The average particle diameter D50 of aerogel particles can be measured by a laser diffraction / scattering method. For example, aerogel particles are added to a solvent (ethanol) so that the content of the aerogel particles is 0.05-5% by mass, and the aerogel particles are dispersed by vibrating with a 50W ultrasonic homogenizer for 15-30 minutes. Then, about 10 mL of the dispersion is injected into a laser diffraction / scattering type particle size distribution measuring device, and the particle size is measured at 25°C, with a refractive index of 1.3 and an absorption of 0. Then, the particle diameter at an integrated value of 50% (volume basis) in this particle size distribution is taken as the average particle diameter D50. As a measuring device, for example, Microtrac MT3000 (manufactured by Nikkiso Co., Ltd., product name) can be used.

[0076] Commercially available aerogel particles may also be used, such as ENOVA MT1100 (manufactured by CABOT) and AeroVa (manufactured by JIOS AEROGEL CORPORATION).

[0077] In this embodiment, the amount of aerogel particles is preferably such that the total content of the aerogel particles and aggregates in the coating liquid is 70% by volume or more, more preferably 72% by volume or more, and even more preferably 74% by volume or more, based on the total volume of the solids. The amount of aerogel particles may be such that the total content of the aerogel particles and aggregates in the coating liquid is, for example, 99% by volume or less, 98% by volume or less, or 97% by volume or less, based on the total volume of the solids.

[0078] <Method of manufacturing aerogel particles> The method for producing the aerogel particles is not particularly limited, but for example, the aerogel particles can be produced by the following method.

[0079] The aerogel particles of this embodiment can be produced by a production method mainly including a sol production process, a wet gel production process in which the sol obtained in the sol production process is gelled and then aged to obtain a wet gel, a washing and solvent replacement process in which the wet gel obtained in the wet gel production process is washed and (if necessary) solvent-replaced, a drying process in which the washed and solvent-replaced wet gel is dried, and a crushing process in which the aerogel obtained by drying is crushed.

[0080] Alternatively, the composition may be produced by a production method mainly including a sol generation step, a wet gel generation step, a wet gel crushing step of crushing the wet gel obtained in the wet gel generation step, a washing and solvent replacement step, and a drying step.

[0081] The size of the obtained aerogel particles can be further uniformed by sieving, classification, etc. By adjusting the particle size, the dispersibility can be improved. In addition, "sol" means a state before the gelation reaction occurs, and in this embodiment, the silicon compound and, in some cases, silica particles are dissolved or dispersed in a solvent. In addition, the wet gel means a gel solid in a wet state that does not have fluidity even though it contains a liquid medium.

[0082] (Sol generation process) The sol generation process is a process in which a silicon compound and, optionally, silica particles (or a solvent containing silica particles) are mixed to carry out a hydrolysis reaction, and then a sol is generated. In this process, an acid catalyst may be further added to the solvent in order to promote the hydrolysis reaction. In addition, as shown in Japanese Patent No. 5250900, a surfactant, a thermally hydrolyzable compound, etc. may also be added to the solvent. Furthermore, for the purpose of suppressing heat radiation, etc., components such as carbon graphite, an aluminum compound, a magnesium compound, a silver compound, and a titanium compound may be added to the solvent.

[0083] As the solvent, for example, water or a mixture of water and alcohol can be used. Examples of alcohol include methanol, ethanol, n-propanol, 2-propanol, n-butanol, 2-butanol, and t-butanol. Among these, examples of alcohol that have low surface tension and low boiling point in terms of reducing the interfacial tension with the gel wall include methanol, ethanol, and 2-propanol. These may be used alone or in combination of two or more.

[0084] For example, when alcohol is used as the solvent, the amount of alcohol can be 4 to 8 mol per mole of the total amount of the silicon compounds and the polysiloxane compounds, but may also be 4 to 6.5, or may also be 4.5 to 6 mol. By making the amount of alcohol 4 mol or more, it becomes easier to obtain good compatibility, and by making it 8 mol or less, it becomes easier to suppress shrinkage of the gel.

[0085] Examples of the acid catalyst include inorganic acids such as hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, hypophosphorous acid, bromic acid, chloric acid, chlorous acid, hypochlorous acid, etc.; acid phosphates such as acid aluminum phosphate, acid magnesium phosphate, and acid zinc phosphate; and organic carboxylic acids such as acetic acid, formic acid, propionic acid, oxalic acid, malonic acid, succinic acid, citric acid, malic acid, adipic acid, and azelaic acid. Among these, an organic carboxylic acid can be mentioned as an acid catalyst that further improves the water resistance of the obtained aerogel. The organic carboxylic acid can be acetic acid, but it can also be formic acid, propionic acid, oxalic acid, malonic acid, etc. These can be used alone or in a mixture of two or more types.

[0086] By using an acid catalyst, the hydrolysis reaction of the silicon compound can be accelerated, and the sol can be obtained in a shorter time.

[0087] The amount of the acid catalyst added may be 0.001 to 0.1 part by mass per 100 parts by mass of the total amount of the polysiloxane compounds and the silicon compounds.

[0088] The surfactant may be a nonionic surfactant, an ionic surfactant, etc. These may be used alone or in combination of two or more kinds.

[0089] As the nonionic surfactant, for example, a compound containing a hydrophilic part such as polyoxyethylene and a hydrophobic part mainly composed of an alkyl group, a compound containing a hydrophilic part such as polyoxypropylene, etc. can be used. Examples of the compound containing a hydrophilic part such as polyoxyethylene and a hydrophobic part mainly composed of an alkyl group include polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene alkyl ether, etc. Examples of the compound containing a hydrophilic part such as polyoxypropylene include polyoxypropylene alkyl ether, block copolymers of polyoxyethylene and polyoxypropylene, etc.

[0090] Examples of the ionic surfactant include cationic surfactant, anionic surfactant, amphoteric surfactant, etc. Examples of the cationic surfactant include cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, etc. Examples of the anionic surfactant include sodium dodecylsulfonate, etc. Examples of the amphoteric surfactant include amino acid surfactant, betaine surfactant, amine oxide surfactant, etc. Examples of the amino acid surfactant include acyl glutamic acid, etc. Examples of the betaine surfactant include lauryl dimethyl amino acetate betaine, stearyl dimethyl amino acetate betaine, etc. Examples of the amine oxide surfactant include lauryl dimethyl amine oxide.

[0091] These surfactants are believed to act to reduce the difference in chemical affinity between the solvent in the reaction system and the growing siloxane polymer in the wet gel formation process described below, thereby suppressing phase separation.

[0092] The amount of the surfactant to be added depends on the type of surfactant or the type and amount of the silicon compound, but can be, for example, 1 to 100 parts by mass per 100 parts by mass of the total amount of the polysiloxane compounds and the silicon compounds, or 5 to 60 parts by mass.

[0093] It is believed that the thermally hydrolyzable compound generates a base catalyst by thermal hydrolysis, makes the reaction solution basic, and promotes the sol-gel reaction in the wet gel production step described below. Therefore, the thermally hydrolyzable compound is not particularly limited as long as it is a compound that can make the reaction solution basic after hydrolysis, and examples of the thermally hydrolyzable compound include urea; acid amides such as formamide, N-methylformamide, N,N-dimethylformamide, acetamide, N-methylacetamide, and N,N-dimethylacetamide; and cyclic nitrogen compounds such as hexamethylenetetramine. Among these, urea is particularly likely to achieve the above-mentioned promotion effect.

[0094] The amount of the thermohydrolyzable compound to be added is not particularly limited as long as it is an amount that can sufficiently promote the sol-gel reaction in the wet gel generation step described below. For example, when urea is used as the thermohydrolyzable compound, the amount of the compound to be added can be 1 to 200 parts by mass relative to 100 parts by mass of the total amount of the polysiloxane compound group and the silicon compound group. The amount of the compound to be added may be 2 to 150 parts by mass. By making the amount of the compound to be added 1 part by mass or more, it becomes easier to obtain good reactivity, and by making the amount of the compound to be added 200 parts by mass or less, it becomes easier to suppress the precipitation of crystals and the decrease in gel density.

[0095] The hydrolysis in the sol production step may be carried out for 10 minutes to 24 hours in a temperature environment of 20 to 60° C., or for 5 minutes to 8 hours in a temperature environment of 50 to 60° C., depending on the types and amounts of the silicon compound, silica particles, acid catalyst, surfactant, etc. in the mixed liquid. This allows the hydrolyzable functional groups in the silicon compound to be sufficiently hydrolyzed, and the hydrolysis product of the silicon compound can be obtained more reliably.

[0096] However, when a thermally hydrolyzable compound is added to the solvent, the temperature environment of the sol generation step may be adjusted to a temperature that suppresses hydrolysis of the thermally hydrolyzable compound and suppresses gelation of the sol. The temperature at this time may be any temperature as long as it can suppress hydrolysis of the thermally hydrolyzable compound. For example, when urea is used as the thermally hydrolyzable compound, the temperature environment of the sol generation step may be 0 to 40°C, but may also be 10 to 30°C.

[0097] (Wet gel production process) The wet gel forming step is a step of gelling the sol obtained in the sol forming step, followed by aging to obtain a wet gel. In this step, a base catalyst can be used to promote gelling.

[0098] Examples of the base catalyst include carbonates such as calcium carbonate, potassium carbonate, sodium carbonate, barium carbonate, magnesium carbonate, lithium carbonate, ammonium carbonate, copper (II) carbonate, iron (II) carbonate, and silver (I) carbonate; hydrogen carbonates such as calcium hydrogen carbonate, potassium hydrogen carbonate, sodium hydrogen carbonate, and ammonium hydrogen carbonate; alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, and cesium hydroxide; ammonium compounds such as ammonium hydroxide, ammonium fluoride, ammonium chloride, and ammonium bromide; basic sodium phosphates such as sodium metaphosphate, sodium pyrophosphate, and sodium polyphosphate; allylamine, diallylamine, triallylamine, isopropylamine, diisopropylamine, ethylamine, diethylamine, Aliphatic amines such as amine, triethylamine, 2-ethylhexylamine, 3-ethoxypropylamine, diisobutylamine, 3-(diethylamino)propylamine, di-2-ethylhexylamine, 3-(dibutylamino)propylamine, tetramethylethylenediamine, t-butylamine, sec-butylamine, propylamine, 3-(methylamino)propylamine, 3-(dimethylamino)propylamine, 3-methoxyamine, dimethylethanolamine, methyldiethanolamine, diethanolamine, and triethanolamine; nitrogen-containing heterocyclic compounds such as morpholine, N-methylmorpholine, 2-methylmorpholine, piperazine and its derivatives, piperidine and its derivatives, and imidazole and its derivatives. Among these, ammonium hydroxide (aqueous ammonia) is highly volatile and does not easily remain in the aerogel particles after drying, so it is not likely to impair water resistance, and is also excellent in terms of economy. The above-mentioned base catalysts may be used alone or in a mixture of two or more types.

[0099] By using a base catalyst, the dehydration condensation reaction or the dealcoholization condensation reaction of the silicon compound and the silica particles in the sol can be promoted, and the gelation of the sol can be performed in a shorter time. This also makes it possible to obtain a wet gel with higher strength (rigidity). In particular, since ammonia is highly volatile and does not easily remain in the aerogel particles, the use of ammonia as a base catalyst makes it possible to obtain aerogel particles with better water resistance.

[0100] The amount of the base catalyst added can be 0.5 to 5 parts by mass, but may be 1 to 4 parts by mass, relative to 100 parts by mass of the total amount of the polysiloxane compounds and the silicon compounds. By making the amount 0.5 parts by mass or more, gelation can be performed in a shorter time, and by making the amount 5 parts by mass or less, the decrease in water resistance can be further suppressed.

[0101] The gelation of the sol in the wet gel generating step may be carried out in a sealed container so that the solvent and the base catalyst do not volatilize. The gelation temperature may be 30 to 90°C, but may be 40 to 80°C. By setting the gelation temperature at 30°C or higher, the gelation can be carried out in a shorter time, and a wet gel with higher strength (rigidity) can be obtained. Furthermore, by setting the gelation temperature at 90°C or lower, it becomes easier to suppress the volatilization of the solvent (especially alcohol), so that gelation can be carried out while suppressing volumetric shrinkage.

[0102] The aging in the wet gel production step may be performed in a sealed container so that the solvent and the base catalyst do not volatilize. The aging strengthens the bonds between the components that make up the wet gel, and as a result, a wet gel with sufficient strength (rigidity) to suppress shrinkage during drying can be obtained. The aging temperature can be 30 to 90°C, but may be 40 to 80°C. By setting the aging temperature at 30°C or higher, a wet gel with higher strength (rigidity) can be obtained, and by setting the aging temperature at 90°C or lower, it becomes easier to suppress the volatilization of the solvent (especially alcohol), so that gelation can be performed while suppressing volumetric shrinkage.

[0103] Incidentally, since it is often difficult to determine the completion time of the gelation of the sol, the gelation of the sol and the subsequent aging may be carried out continuously in a series of operations.

[0104] The gelation time and aging time can be appropriately set depending on the gelation temperature and aging temperature. When silica particles are contained in the sol, the gelation time can be particularly shortened compared to when silica particles are not contained. This is presumably because the silanol group or reactive group of the silicon compound in the sol forms a hydrogen bond or a chemical bond with the silanol group of the silica particles. The gelation time can be 10 to 120 minutes, but may be 20 to 90 minutes. By setting the gelation time to 10 minutes or more, a homogeneous wet gel can be easily obtained, and by setting it to 120 minutes or less, the washing and solvent replacement process to the drying process described later can be simplified. In addition, the total time of the gelation time and aging time as a whole process of gelation and aging can be 4 to 480 hours, but may be 6 to 120 hours. By setting the total of the gelation time and aging time to 4 hours or more, a wet gel with higher strength (rigidity) can be obtained, and by setting it to 480 hours or less, the effect of aging can be more easily maintained.

[0105] In order to reduce the density of the resulting aerogel particles or to increase the average pore size, the gelation temperature and aging temperature may be increased within the above ranges, or the total time of the gelation time and aging time may be increased within the above ranges. In addition, in order to increase the density of the resulting aerogel particles or to decrease the average pore size, the gelation temperature and aging temperature may be decreased within the above ranges, or the total time of the gelation time and aging time may be shortened within the above ranges.

[0106] (Wet gel crushing process) When the wet gel crushing step is performed, the wet gel obtained in the wet gel production step is crushed. The crushing can be performed, for example, by putting the wet gel in a Henshall mixer, or by performing the wet gel production step in a mixer and operating the mixer under appropriate conditions (rotation speed and time). More simply, the wet gel can be placed in a sealable container, or by performing the wet gel production step in a sealable container, and shaking for an appropriate time using a shaking device such as a shaker. If necessary, the particle size of the wet gel can also be adjusted using a jet mill, roller mill, bead mill, or the like.

[0107] (Washing and solvent replacement process) The washing and solvent replacement process includes a process (washing process) of washing the wet gel obtained by the wet gel production process or the wet gel crushing process, and a process (solvent replacement process) of replacing the washing liquid in the wet gel with a solvent suitable for drying conditions (drying process described later). The washing and solvent replacement process can be carried out in a form in which only the solvent replacement process is carried out without performing the process of washing the wet gel, but from the viewpoint of reducing impurities such as unreacted substances and by-products in the wet gel and enabling the production of aerogel particles with higher purity, the wet gel may be washed.

[0108] In the washing step, the wet gel obtained in the wet gel generating step or the wet gel crushing step is washed. The washing can be repeatedly performed using, for example, water or an organic solvent. In this case, the washing efficiency can be improved by heating.

[0109] As the organic solvent, various organic solvents such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, acetone, methyl ethyl ketone, 1,2-dimethoxyethane, acetonitrile, hexane, toluene, diethyl ether, chloroform, ethyl acetate, tetrahydrofuran, methylene chloride, N,N-dimethylformamide, dimethyl sulfoxide, acetic acid, formic acid, etc. The above organic solvents may be used alone or in combination of two or more.

[0110] In the solvent replacement step described below, a solvent with low surface tension can be used to suppress the shrinkage of the gel due to drying. However, a solvent with low surface tension generally has extremely low mutual solubility with water. Therefore, when a solvent with low surface tension is used in the solvent replacement step, the organic solvent used in the washing step can be a hydrophilic organic solvent having high mutual solubility with both water and a solvent with low surface tension. The hydrophilic organic solvent used in the washing step can play the role of preliminary replacement for the solvent replacement step. Among the above organic solvents, examples of hydrophilic organic solvents include methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, etc. In addition, methanol, ethanol, methyl ethyl ketone, etc. are excellent in terms of economy.

[0111] The amount of water or organic solvent used in the washing step can be an amount that can sufficiently replace the solvent in the wet gel and wash it. The amount can be 3 to 10 times the volume of the wet gel. Washing can be repeated until the water content in the wet gel after washing is 10 mass% or less relative to the mass of silica.

[0112] The temperature environment in the washing step can be a temperature equal to or lower than the boiling point of the solvent used in washing. For example, when methanol is used, the temperature can be raised to about 30 to 60°C.

[0113] In the solvent replacement step, the solvent of the washed wet gel is replaced with a predetermined replacement solvent in order to suppress the shrinkage of the aerogel in the drying step. In this case, the replacement efficiency can be improved by heating. Specifically, the replacement solvent may be a low surface tension solvent as described below when drying is performed at a temperature below the critical point of the solvent used for drying in the drying step under atmospheric pressure. On the other hand, when supercritical drying is performed, the replacement solvent may be, for example, ethanol, methanol, 2-propanol, dichlorodifluoromethane, carbon dioxide, or a mixture of two or more of these.

[0114] An example of a solvent with low surface tension is a solvent having a surface tension of 30 mN / m or less at 20° C. The surface tension may be 25 mN / m or less, or 20 mN / m or less. Examples of low surface tension solvents include aliphatic hydrocarbons such as pentane (15.5), hexane (18.4), heptane (20.2), octane (21.7), 2-methylpentane (17.4), 3-methylpentane (18.1), 2-methylhexane (19.3), cyclopentane (22.6), cyclohexane (25.2), and 1-pentene (16.0); aromatic hydrocarbons such as benzene (28.9), toluene (28.5), m-xylene (28.7), and p-xylene (28.3); and halides such as dichloromethane (27.9), chloroform (27.2), carbon tetrachloride (26.9), 1-chloropropane (21.8), and 2-chloropropane (18.1). halogenated hydrocarbons; ethers such as ethyl ether (17.1), propyl ether (20.5), isopropyl ether (17.7), butyl ethyl ether (20.8), 1,2-dimethoxyethane (24.6); ketones such as acetone (23.3), methyl ethyl ketone (24.6), methyl propyl ketone (25.1), diethyl ketone (25.3); esters such as methyl acetate (24.8), ethyl acetate (23.8), propyl acetate (24.3), isopropyl acetate (21.2), isobutyl acetate (23.7), ethyl butyrate (24.6) etc. (The value in parentheses indicates the surface tension at 20℃, in [mN / m]). Among these, aliphatic hydrocarbons (hexane, heptane, etc.) have low surface tension and are excellent in the working environment. Among these, hydrophilic organic solvents such as acetone, methyl ethyl ketone, and 1,2-dimethoxyethane can be used as the organic solvent in the washing step. Among these, solvents having a boiling point of 100° C. or less at normal pressure may be used in terms of ease of drying in the drying step described below. The above solvents may be used alone or in combination of two or more.

[0115] The amount of the solvent used in the solvent replacement step can be an amount that can sufficiently replace the solvent in the wet gel after washing, and can be 3 to 10 times the volume of the wet gel.

[0116] The temperature environment in the solvent substitution step can be a temperature equal to or lower than the boiling point of the solvent used for substitution. For example, when heptane is used, the temperature can be raised to about 30 to 60°C.

[0117] In addition, when silica particles are contained in the gel, the solvent replacement process is not essential. The mechanism is assumed to be as follows. That is, the silica particles function as a support for the three-dimensional mesh-like skeleton, thereby supporting the skeleton and suppressing the shrinkage of the gel in the drying process. Therefore, it is considered that the gel can be directly subjected to the drying process without replacing the solvent used for washing. In this way, by using silica particles, it is possible to simplify the washing and solvent replacement processes to the drying process.

[0118] (drying process) In the drying step, the wet gel washed and (if necessary) solvent-substituted as described above is dried. This allows an aerogel (aerogel block or aerogel particles) to be obtained. That is, an aerogel can be obtained by drying the wet gel produced from the sol.

[0119] The drying method is not particularly limited, and known methods such as normal pressure drying, supercritical drying, or freeze drying can be used. Among these, normal pressure drying or supercritical drying can be used from the viewpoint of ease of manufacturing low-density aerogel. Furthermore, normal pressure drying can be used from the viewpoint of low-cost production. In this embodiment, normal pressure means 0.1 MPa (atmospheric pressure).

[0120] The aerogel can be obtained by drying the wet gel that has been washed and (if necessary) solvent-substituted at atmospheric pressure at a temperature below the critical point of the solvent used for drying. The drying temperature varies depending on the type of substituted solvent (or the solvent used for washing if solvent substitution is not performed), but can be 20 to 150°C, taking into consideration that drying at a high temperature may accelerate the evaporation rate of the solvent and cause large cracks in the gel. The drying temperature may be 60 to 120°C. The drying time varies depending on the volume of the wet gel and the drying temperature, but can be 4 to 120 hours. It should be noted that drying at normal pressure also includes applying a pressure below the critical point to accelerate drying within a range that does not impair productivity.

[0121] The aerogel can also be obtained by subjecting a wet gel that has been washed and (if necessary) solvent-substituted to supercritical drying. Supercritical drying can be performed by a known method. Examples of the supercritical drying method include a method of removing the solvent at a temperature and pressure equal to or higher than the critical point of the solvent contained in the wet gel, or a method of supercritical drying includes a method of immersing the wet gel in liquefied carbon dioxide under conditions of, for example, 20 to 25°C and about 5 to 20 MPa to replace all or a part of the solvent contained in the wet gel with carbon dioxide having a lower critical point than the solvent, and then removing the carbon dioxide alone or a mixture of carbon dioxide and the solvent.

[0122] The aerogel obtained by such normal pressure drying or supercritical drying may be further dried at normal pressure at 105 to 200°C for about 0.5 to 2 hours. This makes it easier to obtain an aerogel with low density and small pores. The additional drying may be performed at normal pressure at 150 to 200°C.

[0123] (Crushing process) When the wet gel crushing step is not performed, the aerogel obtained by drying (aerogel block) is crushed to obtain aerogel particles. For example, this can be done by putting the aerogel into a jet mill, roller mill, bead mill, hammer mill, etc., and operating it at an appropriate rotation speed for an appropriate time.

[0124] <Water-soluble polymer> In this embodiment, the water-soluble polymer may have a hydrophobic group and be water-soluble.

[0125] Examples of the hydrophobic group include an alkyl group (preferably a long-chain alkyl group having 6 to 26 carbon atoms), an ester group, an alkoxy group, a halogen, etc. Among these, the hydrophobic group is preferably an alkyl group, more preferably a long-chain alkyl group having 8 to 26 carbon atoms, still more preferably a long-chain alkyl group having 10 to 26 carbon atoms, still more preferably a long-chain alkyl group having 12 to 26 carbon atoms, and may be a long-chain alkyl group having 15 to 26 carbon atoms.

[0126] Examples of the water-soluble polymer include modified carboxyl vinyl polymers, modified polyether urethane, cellulose-based resins, polyethylene oxide, polyvinyl alcohol, polyacrylates, polyvinylpyrrolidone, dextrin-based resins, chitin-based resins, and chitosan-based resins.

[0127] As the water-soluble polymer, a cellulose-based resin can be suitably used, such as methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and modified products obtained by further modifying these (e.g., hydrophobizing them), etc.

[0128] The cellulose-based resin is preferably a cellulose-based resin having an alkyl group, more preferably a cellulose-based resin having a long-chain alkyl group having 6 to 26 carbon atoms. With such a cellulose-based resin, the effects of the present invention are more pronounced. The carbon number of the long-chain alkyl group is preferably 8 to 26, more preferably 10 to 26, even more preferably 12 to 26, and even more preferably 15 to 26.

[0129] The cellulose-based resin is preferably, for example, a cellulose-based resin having a structural unit represented by the following formula (A-1).

[0130] [ka]

[0131] In formula (A-1), R A is a hydrogen atom, an alkyl group, a hydroxyalkyl group, -R A1 -OR A2 A group represented by R A1 represents an alkanediyl group or a hydroxyalkanediyl group, R A2 represents an alkyl group.) Three R A may be the same or different from each other. However, three R A At least one of the groups is an alkyl group or -R A1 -OR A2 It is a group represented by the following formula:

[0132] In formula (A-1), R A The alkyl group in R is preferably an alkyl group having 1 to 26 carbon atoms. A The alkyl group in is more preferably a short-chain alkyl group having 1 to 3 carbon atoms, or a long-chain alkyl group having 6 to 26 carbon atoms. The long-chain alkyl group preferably has 8 to 26 carbon atoms, more preferably 10 to 26 carbon atoms, even more preferably 12 to 26 carbon atoms, and even more preferably 15 to 26 carbon atoms.

[0133] In formula (A-1), R AThe hydroxyalkyl group in is preferably a hydroxyalkyl group having 1 to 26 carbon atoms, more preferably a hydroxyalkyl group having 1 to 10 carbon atoms, and further preferably a hydroxyalkyl group having 1 to 5 carbon atoms.

[0134] In formula (A-1), R A1 The alkanediyl group in R is preferably an alkanediyl group having 1 to 26 carbon atoms, more preferably an alkanediyl group having 1 to 10 carbon atoms, and further preferably an alkanediyl group having 1 to 5 carbon atoms. A1 The hydroxyalkanediyl group in the formula (I) is preferably a hydroxyalkanediyl group having 1 to 26 carbon atoms, more preferably a hydroxyalkanediyl group having 1 to 10 carbon atoms, and even more preferably a hydroxyalkanediyl group having 1 to 5 carbon atoms.

[0135] In formula (A-1), R A2 is preferably an alkyl group having 1 to 26 carbon atoms. A2 The alkyl group in is preferably a short-chain alkyl group having 1 to 3 carbon atoms or a long-chain alkyl group having 6 to 26 carbon atoms, and more preferably a long-chain alkyl group. The long-chain alkyl group preferably has 8 to 26 carbon atoms, more preferably 10 to 26 carbon atoms, even more preferably 12 to 26 carbon atoms, and even more preferably 15 to 26 carbon atoms.

[0136] In formula (A-1), three R A At least one of the R A At least one of them is -R A1 -OR A2 and R A2 is preferably a long chain alkyl group.

[0137] In the cellulose-based resin, the content of long-chain alkyl groups having 6 to 26 carbon atoms is preferably 0.01 to 5 mass %, and more preferably 0.01 to 3 mass %, based on the total amount of the cellulose-based resin.

[0138] In this embodiment, the content of the water-soluble polymer in the coating liquid may be, for example, 0.01% by volume or more, preferably 0.1% by volume or more, and more preferably 0.3% by volume or more, based on the total volume of the solid content in the coating liquid. The content of the water-soluble polymer may be, for example, 10% by volume or less, preferably 5% by volume or less, and more preferably 3% by volume or less, based on the total volume of the solid content in the coating liquid.

[0139] <Liquid medium> As the liquid medium, an aqueous solvent containing water is preferable. The aqueous solvent may contain an organic solvent other than water. The organic solvent may be any one that is compatible with water, and examples thereof include alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, and propylene glycol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone and methyl ethyl ketone; carboxylic acids such as acetic acid and propionic acid; and nitrogen-containing compounds such as acetonitrile, dimethylformamide, and triethylamine.

[0140] In this embodiment, the content of the liquid medium in the coating liquid is not particularly limited and may be appropriately changed depending on the desired viscosity of the coating liquid, etc. For example, the content of the liquid medium may be an amount that brings the solid content of the coating liquid into a suitable range described below.

[0141] The solid content of the coating liquid may be, for example, 10% by mass or more, preferably 15% by mass or more, and more preferably 20% by mass or more. The solid content of the coating liquid may be, for example, 70% by mass or less, preferably 60% by mass or less, and more preferably 50% by mass or less.

[0142] <Other ingredients> In this embodiment, the coating liquid may further contain components other than the aerogel particles, the water-soluble polymer, and the liquid medium.

[0143] The coating liquid according to the present embodiment may further contain, for example, a binder resin. Examples of the binder resin include epoxy resin, silicone resin, phenol resin, urea resin, melamine resin, polyurethane resin, polyethylene resin, polypropylene resin, polystyrene resin, polyester resin, acrylic resin, polyvinyl chloride resin, polyvinyl acetate resin, polyamide resin, polyimide resin, polyvinyl resin, etc. Among these, silicone resin, acrylic resin, phenol resin, polyester resin, etc. can be preferably used from the viewpoint of heat resistance and toughness.

[0144] In this embodiment, when the coating liquid contains a binder resin, the content of the binder resin in the coating liquid may be, for example, 30% by volume or less, preferably 28% by volume or less, and more preferably 25% by volume or less, based on the total volume of the solid content. The content of the binder resin in the coating liquid may be, for example, 0.1% by volume or more, or 1% by volume or more, based on the total volume of the solid content.

[0145] Furthermore, the composite material according to this embodiment may further contain, as components other than those described above, a thickener, a fibrous substance, a pigment, a leveling agent, and the like.

[0146] Examples of the thickener include fine particles of fumed silica, clay minerals, and the like.

[0147] The fibrous material can exert an anchor function between aerogel particles, and can further improve the strength of the coating film made of the composite material. The fibrous material is not particularly limited, and examples thereof include organic fibers and inorganic fibers. Examples of organic fibers include polyamide fibers, polyimide fibers, polyvinyl alcohol fibers, polyvinylidene chloride fibers, polyvinyl chloride fibers, polyester fibers, polyacrylonitrile fibers, polyethylene fibers, polypropylene fibers, polyurethane fibers, phenolic fibers, polyether ester fibers, polylactic acid fibers, polycarbonate fibers, etc. Examples of inorganic fibers include glass fibers, carbon fibers, ceramic fibers, metal fibers, etc.

[0148] <Method of producing coating fluid> In this embodiment, the coating liquid is produced by a production method including a preparation step of preparing aerogel particles, a water-soluble polymer, and a liquid medium, and a mixing step of mixing the aerogel particles, the water-soluble polymer, and the liquid medium prepared in the preparation step to agglomerate the aerogel particles, thereby obtaining a coating liquid containing agglomerates of aerogel particles, the water-soluble polymer, and the liquid medium.

[0149] In the preparation step, components other than the aerogel particles, the water-soluble polymer, and the liquid medium (for example, the components described in the above <Other Components>) may be further prepared.

[0150] In the mixing step, the components prepared in the preparation step are mixed so that the aerogel particles are aggregated. The mixing method may be any method that can form an aggregate of the aerogel particles, and may be, for example, a method of stirring and mixing the components prepared in the preparation step.

[0151] The stirring speed affects the size of the aggregates. The higher the stirring speed, the more shear stress is applied to the coating liquid, and the smaller the size of the aggregates tends to be. Therefore, from the viewpoint of obtaining aggregates of a suitable size as described below, it is desirable to prepare the coating liquid at a low stirring speed.

[0152] In addition, the viscosity during mixing also affects the size of the aggregates. Even at the same stirring speed, the shear stress applied to the coating liquid changes depending on the viscosity. If the viscosity is high, a larger shear stress is applied to the coating liquid, and the aggregates become smaller in size. On the other hand, if the viscosity of the coating liquid is low, even at the same stirring speed, the shear stress applied to the coating liquid becomes smaller, and the aggregates become larger. Therefore, by adjusting the stirring speed depending on the viscosity of the coating liquid, a coating liquid with a desired aggregate size can be produced.

[0153] The size of the aggregates can also be changed by using additives. Examples of additives that have a strong effect on the size of the aggregates include surface conditioners, surfactants, dispersants, and emulsion resins.

[0154] The surface modifier and surfactant lower the surface energy between the aerogel particles and the solution. The lower the surface energy, the weaker the force that tries to reduce the interface, and the smaller the size of the aggregates tends to be. Therefore, the addition of the surface modifier and surfactant lowers the surface energy and reduces the size of the aggregates.

[0155] A dispersant adheres to the surface of a particle and inhibits the approach of the particles by electrostatic or steric repulsion. Since a dispersant adheres to the surface of aerogel particles and inhibits the approach of aerogel particles, the addition of a dispersant reduces the size of the aggregates.

[0156] Emulsion resin is a resin dispersed in water mainly by a dispersant. Such emulsion resin is adsorbed on the surface of aerogel particles, and the accompanying dispersant prevents the aerogel particles from approaching each other. In other words, the addition of emulsion resin reduces the size of the aggregates.

[0157] In addition, the amount of liquid medium used during mixing also affects the size of the aggregates. Even if the composition of the coating liquid finally produced is the same, the size of the aggregates differs between (i) a method in which the entire amount of the liquid medium is added from the beginning of mixing and (ii) a method in which a small amount of liquid medium is mixed in the beginning of mixing and then the liquid medium is added. Compared to the method (i), the method (ii) above has a higher initial coating liquid viscosity, and when the above-mentioned additives are added, the concentration of the additives is also higher. Therefore, the method (ii) above tends to produce smaller aggregates than the method (i). By using these methods appropriately according to the conditions of the coating liquid composition, the mixing device (stirring device), etc., aggregates of the desired size can be formed.

[0158] The larger the size of the aggregates, the smaller the contact interface between the aerogel and the resin component, and the more easily the penetration of the resin component into the pores of the aerogel is suppressed. From this viewpoint, in this embodiment, it is preferable that aggregates having a diameter of 20 μm or more are formed, more preferably that aggregates having a diameter of 40 μm or more are formed, and even more preferably that aggregates having a diameter of 50 μm or more are formed. On the other hand, from the viewpoint of avoiding a decrease in film strength due to the continuation of relatively fragile aerogel, the diameter of the aggregates is preferably 400 μm or less, and more preferably 300 μm or less.

[0159] In this embodiment, the average diameter of the aggregates is preferably 2 times or more, more preferably 4 times or more, and even more preferably 8 times or more, of the average diameter of the aerogel particles prepared in the preparation step. This makes the contact interface between the aerogel and the resin component smaller, and makes it easier to suppress the penetration of the resin component into the pores of the aerogel. In addition, the average diameter of the aggregates is preferably 40 times or less, more preferably 30 times or less, and even more preferably 20 times or less, of the average diameter of the aerogel particles prepared in the preparation step. This suppresses the decrease in film strength due to the continuity of relatively fragile aerogel, making it easier to obtain a higher film strength.

[0160] In this specification, the average diameter of the aggregates indicates a value measured by the following method. [Method for measuring the average diameter of aggregates in coating liquid] Put about 20 g of the coating liquid into a 100 mL plastic cup, and gradually dilute it by adding 2 g of water at a time while stirring with a spatula. Place the diluted sample on a glass plate and take a micrograph of the sample using an optical microscope (OLYMPUS, model number: BX51). Analyze the obtained micrograph using the image editing software ImageJ to determine the diameter of multiple aggregates in the micrograph. The average of the obtained values ​​is taken as the average diameter of the aggregates.

[0161] In this specification, the average diameter of the aerogel particles is synonymous with the above-mentioned average particle diameter D50 of the aerogel particles.

[0162] In this embodiment, when the diluted solution obtained by diluting the coating liquid is observed with an optical microscope, the area occupied by aggregates having a diameter of 20 μm or more (more preferably aggregates having a diameter of 50 μm or more) of the area occupied by aerogel particles and aggregates within the observation field of view is preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, and may even be 100%.

[0163] In this specification, the diluted solution obtained by diluting the coating solution and the observation method of the diluted solution may be the same as the sample prepared in the above-mentioned [Method for measuring the average diameter of aggregates in the coating solution] and the observation method of the sample. In addition, the "area within the observation field of view" is determined by analyzing the micrograph using the image editing software ImageJ.

[0164] <Insulation material manufacturing method> In this embodiment, the heat insulating material is produced by a production method including a coating step of applying the coating liquid onto a support to obtain a coating film, and a removal step of removing at least a part of the liquid medium from the coating film to obtain a heat insulating material. According to this production method, an aggregate of aerogel particles is formed in the coating liquid, and the penetration of the resin into the aerogel pores is sufficiently suppressed, so that a heat insulating material having high heat insulating properties and high film forming properties can be obtained.

[0165] The support to which the coating liquid is applied is not particularly limited. The support may be peeled off from the heat insulating material after the heat insulating material is manufactured, or may be used without peeling off from the heat insulating material. The support may be, for example, the object to which the heat insulating material is applied. The material constituting the support is not particularly limited, and may be, for example, metal, ceramic, glass, resin, composite material thereof, or the like. The form of the support may be appropriately selected according to the purpose of use, material, etc., and may be, for example, block-shaped, sheet-shaped, powder-shaped, fibrous, or the like.

[0166] The method for applying the coating liquid is not particularly limited, and examples thereof include dip coating, spray coating, spin coating, and roll coating.

[0167] The coating method of the coating liquid is preferably a coating method in which the pressure applied to the coating liquid is 1.5 MPa or less. According to such a coating method, the disintegration of aggregates in the coating liquid due to the load during coating is suppressed, and the above-mentioned effects are more prominently exhibited. For example, coating methods such as roller coating, trowel coating, and air spray are preferable because they are easy to reduce the pressure applied to the coating liquid.

[0168] In the removing step, at least a portion of the liquid medium is removed from the coating film to form a heat insulating material made of a composite material containing aggregates of aerogel particles and a water-soluble resin.

[0169] The method for removing the liquid medium from the coating is not particularly limited, and examples thereof include a heating treatment (eg, 40 to 150° C.), a reduced pressure treatment (eg, 10,000 Pa or less), or both of these treatments.

[0170] The thickness of the heat insulating material is not particularly limited and may be, for example, 0.01 to 30 mm, or may be 0.1 to 20 mm.

[0171] The insulation material has pores due to aerogel particles. The pore volume of the insulation material is set to 0.15 cm3 in order to obtain higher insulation properties. 3 / g or more is preferable, and 0.20 cm 3 / g or more is more preferable, and 0.60 cm 3 / g or more is more preferable. The upper limit of the pore volume of the heat insulating material is not particularly limited. The pore volume of the heat insulating material is, for example, 5.0 cm 3 / g or less.

[0172] The thermal conductivity of the insulating material is, for example, 0.05 W / (m·K) or less, preferably 0.04 W / (m·K) or less, and more preferably 0.035 W / (m·K) or less. There is no particular lower limit to the thermal conductivity of the insulating material. The thermal conductivity of the insulating material may be, for example, 0.01 W / (m·K) or more.

[0173] The heat insulating material produced by the production method of this embodiment has excellent heat insulating properties, heat resistance, flame retardancy, etc., derived from the aerogel. Therefore, the heat insulating material can be applied to applications such as heat insulating materials in cryogenic containers, the space field, the construction field, the automobile field, the home appliance field, the semiconductor field, industrial facilities, etc. In addition to its application as a heat insulating material, the heat insulating material can also be used as a water repellent material, a sound absorbing material, a vibration silencing material, a catalyst carrier material, etc.

[0174] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES

[0175] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0176] Example 1 In a 500mL separable flask, 6 parts by mass of Sangelose 90L (manufactured by Daido Chemical Industry Co., Ltd.) as a water-soluble polymer, 46 parts by mass of isopropyl alcohol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., reagent), and 840 parts by mass of hot water were taken, and the mixture was stirred at 200 rpm using a mechanical stirrer for 1 minute to obtain a dispersion. Next, while cooling the flask in an ice-water bath, the mixture was stirred at 200 rpm using a mechanical stirrer to dissolve Sangelose 90L, and a pregel, which is an aqueous solution of Sangelose 90L, was obtained. In a planetary mixer (manufactured by Primix, 2P-1 type), 892 parts by mass of the pregel and 1000 parts by mass of an acrylic resin emulsion aqueous solution (manufactured by DIC Corporation, product name: Boncoat DV759-EF) were taken and stirred at 100 rpm. Next, 100 parts by mass of aerogel particles (manufactured by CABOT, product name: ENOVA MT1100, particle diameter 2-24 μm, average particle diameter (D50) 10 μm) were added, and then the mixture was stirred at 100 rpm to obtain a coating liquid. In the coating liquid, the content of aerogel particles was 74.7 vol%, the content of water-soluble polymer was 0.4 vol%, and the content of acrylic resin was 24.9 vol%, based on the total volume of solids.

[0177] Example 2 The coating liquid of Example 1 was placed in a 150 mL Tight Boy TB-2 (manufactured by AS ONE Corporation) and stirred at 1000 rpm for 5 minutes using a planetary centrifugal mixer (manufactured by THINKY, product name: Awatori Rentaro, model number: ARE-310) to obtain the coating liquid of Example 2.

[0178] Example 3 A dispersion was obtained in the same manner as in Example 1, except that the amount of the water-soluble polymer was changed to 5 parts by mass, the amount of isopropyl alcohol was changed to 80 parts by mass, the amount of hot water was changed to 950 parts by mass, and 20 parts by mass of glass fiber (manufactured by Nitto Boseki Co., Ltd., product name: CS 3J-891) was further added. A pregel was obtained from the dispersion in the same manner as in Example 1. A coating liquid was obtained in the same manner as in Example 1, except that this pregel was used, the amount of the acrylic resin emulsion aqueous solution was changed to 500 parts by mass, and the stirring speed and stirring time after the addition of the aerogel particles were changed to 100 rpm and 60 minutes. In addition, the content of the aerogel particles was 84.85 vol%, the content of the water-soluble polymer was 0.35 vol%, the content of the acrylic resin was 14.14 vol%, and the content of the glass fiber was 0.65 vol%, based on the total volume of the solid content in the coating liquid.

[0179] Example 4 A coating liquid was obtained in the same manner as in Example 3, except that the water-soluble polymer was changed to 5 parts by mass of Marpolose MP-30000 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.), the amount of isopropyl alcohol was changed to 40 parts by mass, and the stirring speed and stirring time after the addition of the aerogel particles were changed to 25 rpm and 15 minutes. In addition, in the coating liquid, the content of the aerogel particles was 84.85 vol%, the content of the water-soluble polymer was 0.35 vol%, the content of the acrylic resin was 14.14 vol%, and the content of the glass fiber was 0.65 vol%, based on the total volume of the solid content.

[0180] Example 5 A coating liquid was obtained in the same manner as in Example 3, except that the water-soluble polymer was changed to 5 parts by mass of Marpolose MP-30000 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.), the amount of isopropyl alcohol was changed to 880 parts by mass, and the stirring speed and stirring time after the addition of the aerogel particles were changed to 100 rpm and 90 minutes. In addition, in the coating liquid, the content of the aerogel particles was 84.85 vol%, the content of the water-soluble polymer was 0.35 vol%, the content of the acrylic resin was 14.14 vol%, and the content of the glass fiber was 0.65 vol%, based on the total volume of the solid content.

[0181] Example 6 A dispersion was obtained in the same manner as in Example 1, except that the amount of the water-soluble polymer was changed to 50 parts by mass, the amount of isopropyl alcohol was changed to 80 parts by mass, the amount of hot water was changed to 1900 parts by mass, and 40 parts by mass of glass fiber (manufactured by Nitto Boseki Co., Ltd., product name: CS 3J-891) was further added. A pregel was obtained from the dispersion in the same manner as in Example 1. A coating liquid was obtained in the same manner as in Example 1, except that this pregel was used, the amount of the acrylic resin emulsion aqueous solution was changed to 500 parts by mass, and the stirring speed and stirring time after the addition of the aerogel particles were changed to 50 rpm and 30 minutes. In addition, the content of the aerogel particles was 81.72 vol%, the content of the water-soluble polymer was 3.40 vol%, the content of the acrylic resin was 13.62 vol%, and the content of the glass fiber was 1.26 vol%, based on the total volume of the solid content in the coating liquid.

[0182] Example 7 A coating liquid was obtained in the same manner as in Example 3, except that the amount of isopropyl alcohol was changed to 160 parts by mass. In the coating liquid, the content of aerogel particles was 84.85% by volume, the content of water-soluble polymer was 0.35% by volume, the content of acrylic resin was 14.14% by volume, and the content of glass fiber was 0.65% by volume, based on the total volume of solids.

[0183] Example 8 A coating liquid was obtained in the same manner as in Example 3, except that the amount of glass fiber was changed to 50 parts by mass, and the stirring speed and stirring time after the addition of the aerogel particles were changed to 25 rpm and 30 minutes, respectively. In the coating liquid, the content of the aerogel particles was 84.03 vol%, the content of the water-soluble polymer was 0.35 vol%, the content of the acrylic resin was 14.00 vol%, and the content of the glass fiber was 1.62 vol%, based on the total volume of the solid content.

[0184] Example 9 As the water-soluble polymer, 10 parts by mass of Sangelose 90L (manufactured by Daido Chemical Industry Co., Ltd.) and 10 parts by mass of Marporose MP-30000 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.) were used, the amount of isopropyl alcohol was changed to 160 parts by mass, the amount of hot water was changed to 2800 parts by mass, the amount of glass fiber was changed to 40 parts by mass, the amount of acrylic resin emulsion aqueous solution was changed to 600 parts by mass, and the stirring speed and stirring time after the addition of aerogel particles were changed to 50 rpm and 30 minutes, respectively. A coating liquid was obtained in the same manner as in Example 3. In addition, based on the total volume of solids in the coating liquid, the content of aerogel particles was 81.17% by volume, the content of water-soluble polymer was 1.35% by volume, the content of acrylic resin was 16.23% by volume, and the content of glass fiber was 1.25% by volume.

[0185] Example 10 As the water-soluble polymer, 4 parts by mass of Sangelose 90L (manufactured by Daido Chemical Industry Co., Ltd.) and 4 parts by mass of Marporose MP-30000 (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.) were used, the amount of isopropyl alcohol was changed to 16 parts by mass, the amount of hot water was changed to 100 parts by mass, the amount of the acrylic resin emulsion aqueous solution was changed to 80 parts by mass, and the stirring speed and stirring time after the addition of the aerogel particles were changed to 50 rpm and 30 minutes, respectively. A coating liquid was obtained in the same manner as in Example 1. In addition, based on the total volume of the solid content in the coating liquid, the content of the aerogel particles was 96.77% by volume, the content of the water-soluble polymer was 0.65% by volume, and the content of the acrylic resin was 2.58% by volume.

[0186] Example 11 A coating liquid was obtained in the same manner as in Example 1, except that the amount of the water-soluble polymer was changed to 5 parts by mass, the amount of isopropyl alcohol was changed to 40 parts by mass, the amount of hot water was changed to 950 parts by mass, the amount of the acrylic resin emulsion aqueous solution was changed to 50 parts by mass, and the stirring speed and stirring time after the addition of the aerogel particles were changed to 50 rpm and 60 minutes. In addition, in the coating liquid, the content of the aerogel particles was 97.96 vol%, the content of the water-soluble polymer was 0.41 vol%, and the content of the acrylic resin was 1.63 vol%, based on the total volume of the solid content.

[0187] Example 12 A coating liquid was obtained in the same manner as in Example 11, except that the amount of the acrylic resin emulsion aqueous solution was changed to 1250 parts by mass, and the stirring speed and stirring time after the addition of the aerogel particles were changed to 50 rpm and 30 minutes, respectively. In the coating liquid, the content of the aerogel particles was 70.38% by volume, the content of the water-soluble polymer was 0.29% by volume, and the content of the acrylic resin was 29.33% by volume, based on the total volume of the solid content.

[0188] Comparative Example 1 The coating liquid of Example 1 was placed in a 150 mL Tight Boy TB-2 (manufactured by AS ONE Corporation) and stirred at 1500 rpm for 5 minutes using a planetary centrifugal mixer (manufactured by THINKY, product name: Awatori Rentaro, model number: ARE-310) to obtain the coating liquid of Comparative Example 1.

[0189] Comparative Example 2 The coating liquid of Example 1 was placed in a 150 mL Tight Boy TB-2 (manufactured by AS ONE Corporation) and stirred at 2000 rpm for 5 minutes using a planetary centrifugal mixer (manufactured by THINKY, product name: Awatori Rentaro, model number: ARE-310) to obtain the coating liquid of Comparative Example 2.

[0190] The coating liquids of Examples 1 to 12 and Comparative Examples 1 and 2 were evaluated by the following methods. The results are shown in Tables 1 to 3.

[0191] <Microscopic observation of coating fluid> Approximately 20 g of the coating liquid was placed in a 100 mL polycup, and water was added in 2 g portions while stirring with a spatula, gradually diluting the mixture. The diluted sample was placed on a glass plate, and the aerogel particles and their aggregates in the coating liquid were observed using an optical microscope (OLYMPUS, model number: BX51), and micrographs were obtained. The micrographs obtained were analyzed using the image editing software ImageJ, and the average diameter of the aerogel particle aggregates was determined.

[0192] <Crack evaluation of insulation material> A frame made of fluororesin measuring 40 mm in length, width and thickness 2 mm was prepared on an aluminum foil (manufactured by UACJ Corporation, product name: My Foil Thick Type 50, thickness: 50 μm), and the coating liquid was applied to the inside of the frame using a spatula. The insulation was left for 12 hours at room temperature of 23°C, and the liquid medium was removed from the coating liquid to obtain an insulating material. The obtained insulating material was evaluated for cracking, with A for those without cracks throughout the insulation, B for those with cracks in some areas, and C for those with cracks throughout.

[0193] <Evaluation of pore volume of insulation material> The insulation material was prepared in the same manner as in the above <Crack evaluation of insulation material>. 100 mg of the prepared insulation material was sampled, and the pore volume was calculated using a high-sensitivity gas adsorption analyzer (Quantachrome, AutoSorb iQ).

[0194] <Evaluation of thermal conductivity of insulation materials> A frame made of fluororesin measuring 200 mm in length and width and 3 mm in thickness was prepared on an aluminum foil (manufactured by UACJ Corporation, product name: My Foil Thick Type 50, thickness: 50 μm), and the coating liquid was applied to the inside of the frame using a spatula. The coating was left for 12 hours at room temperature of 23°C to remove the liquid medium from the coating liquid, yielding a thermal insulation material. The thermal conductivity of the obtained thermal insulation material was measured by a steady-state method using a thermal conductivity measuring device "HFM-446" (manufactured by NETZSCH, product name).

[0195] The amount of each component in Examples 1 to 12 and Comparative Examples 1 and 2 ((1) in the table, parts by mass), the content of each component in the coating liquid ((2) in the table, volume % based on the total volume of the solid content), and the evaluation results are shown in Tables 1 to 3.

[0196] [Table 1]

[0197] [Table 2]

[0198] [Table 3]

[0199] As shown in Tables 1 to 3, in Examples 1 to 12, high pore volume and high heat insulation were achieved, and cracks during film formation were also suppressed. On the other hand, in Comparative Examples 1 and 2, no aggregates larger than aerogel particles were observed, the pore volume was small, the thermal conductivity was high, and cracks occurred throughout the film during formation.

Claims

1. A preparation step of preparing aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium; a mixing step of mixing the aerogel particles, the water-soluble polymer, and the liquid medium prepared in the preparation step to aggregate the aerogel particles and obtain a coating liquid containing the aggregates of the aerogel particles, the water-soluble polymer, and the liquid medium; A method for producing a coating liquid comprising the steps of:

2. 2. The method according to claim 1, wherein the average diameter of the aggregates is 2 to 40 times the average diameter of the aerogel particles prepared in the preparing step.

3. 3. The manufacturing method according to claim 1 or 2, wherein, when a diluted solution obtained by diluting the coating liquid is observed under an optical microscope, an area occupied by the aerogel particles and the agglomerates having a diameter of 20 μm or more is 50% or more of an area occupied by the aerogel particles and the agglomerates within an observation field.

4. The method according to any one of claims 1 to 3, wherein a total content of the aerogel particles and the aggregates in the coating liquid is 70 volume % or more based on a total volume of solids.

5. The method according to any one of claims 1 to 4, wherein the water-soluble polymer comprises a cellulose-based resin.

6. A coating step of applying the coating liquid produced by the production method according to any one of claims 1 to 5 onto a support to obtain a coating film; a removing step of removing at least a portion of the liquid medium from the coating film to obtain a thermal insulating material; A method for producing an insulating material, comprising:

7. The pore volume of the insulating material is 0.15 cm 3 The method according to claim 6, wherein the molecular weight of the polymer is 1 / g or more.

8. A coating liquid containing an aggregate of aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium, When a diluted solution obtained by diluting the coating liquid is observed under an optical microscope, an area occupied by the aerogel particles and the agglomerates within the observation field is 50% or more of an area occupied by the aerogel particles and the agglomerates having a diameter of 20 μm or more.

Citation Information

Patent Citations

  • Oily cosmetic for lip

    JP2008031044A

  • aerogel

    JP2012091943A

  • Heat insulating material and method for producing the same

    JP2014035044A

  • Hair dye

    JP2017210446A

  • Aqueous dispersion of hydrophobic silica aerogel particles, solid composite material, heat insulating material and sound absorbing material

    JP2018043927A